Which firms use trademarks? Firm-level evidence from Germany on the role of distance, product quality and innovation - Dirk Crass (Industry and Innovation, 2020)
Trademarking firms are more productive, generate higher profits, and have a better survival rate. Trademarking firms are in one word more successful, which might motivate non-trademarking firms to adopt a trademark strategy. But this does not seem to be the case. The proportion of trademarking firms in the German business sector amounts to just 18%. This figure is quite low, given that nearly each firm has reputation to protect. But why does the vast majority of firms not have registered trademarks? Using a representative sample of German firms, the present paper links certain firm characteristics to a firm's propensity to register trademarks. The empirical results point to circumstances under which trademarks are significantly more often used: this is the case where a large distance between a firm and its customers exists, a firm's product quality is difficult to assess, a firm's products are characterised by a limited (but not strong) substitutability, and where a firm is engaged in R&D and introduces innovative products. Trademarks are considerably less frequently used if none of this is the case.
Keywords: C25; D21; L14; O34; 330; Intellectual Property Rights; trademarks; reputation; innovation